Nonalcoholic fatty liver disease prevalence and severity in Asian Americans from the national health and nutrition examination surveys 2017–2018. Issue 9 (9th May 2022) - Truong, Emily; Yeo, Yee Hui; Cook‐Wiens, Galen; Muthiah, Mark; Yang, Ju Dong; Sundaram, Vinay; Chang, Devon; Todo, Tsuyoshi; Kim, Irene K.; Lu, Shelly C.; Setiawan, Veronica Wendy; Wong, Vincent W. S.; et al.
Abstract: Studies have examined nonalcoholic fatty liver disease (NAFLD) prevalence and severity in Asians; however, this is not well understood in Asian Americans (both East and South Asian Americans) as few studies have analyzed this population. We aimed to describe characteristics, prevalence of NAFLD, and its severity in Asian Americans in the National Health and Nutrition Examination Surveys (NHANES) from 2017 to 2018. Respondents 18 years and older with interview, laboratory testing, and transient elastography data were included. Other causes of liver disease were excluded. Controlled attenuation parameter (CAP) cutoff ≥ 274 dB/m, as published in the literature, defined NAFLD. Sensitivity analysis for CAP cutoffs ≥ 248 and ≥302 dB/m were performed. We found that 450 out of 3639 respondents were Asian Americans, and prevalence using CAP ≥ 274 dB/m was 43.23%. Using sensitivity analysis cutoffs of CAP ≥ 248 dB/m and CAP ≥ 302 dB/m, the prevalence was 57.38% and 28.03%, respectively. Compared with non‐Asian Americans with NAFLD, Asian Americans with NAFLD had significantly lower body mass index (BMI) and less prevalent smoking history. Comorbidities, such as prediabetes, diabetes, and hypertension, were not significantly different between Asian and non‐Asian Americans with NAFLD. Compared to non‐Asian Americans with NAFLD, Asian Americans with NAFLD exhibited higher aminotransferases and triglycerides. Fibrosis assessed by transient elastography was not significantly different between Asian and non‐Asian Americans with NAFLD. Despite decreased prevalence of BMI ≥ 30 kg/m 2, Asian Americans experienced similar NAFLD prevalence with increased hepatocellular injury and triglyceridemia compared to non‐Asian Americans. Fibrosis stages were similar to non‐Asian Americans. Abstract : This study aimed to describe characteristics, prevalence of NAFLD, and its severity in Asian Americans in the National Health and Nutrition Examination Surveys (NHANES) from 2017 to 2018. Despite younger age, lower BMI cutoffs, and decreased prevalence of obesity compared to non‐Asian Americans with NAFLD, Asian Americans demonstrate similar prevalence of NAFLD with comparable severity of disease as evidenced by the FibroScan‐AST (FAST) score, prevalence of FAST score ≥ 0.67, and liver stiffness measurement on vibration controlled transient elastography.image